1995
DOI: 10.1557/proc-377-27
|View full text |Cite
|
Sign up to set email alerts
|

Power Feeding in Large Area PECVD of Amorphous Silicon

Abstract: Plasma processes are usually worked out in a small-scale environment (electrode area maximum 121 cm2, rf- and VHF- excitation frequencies). In order to meet the requirements of large area device applications they have to be upscaled. The investigations of glow discharge systems for different PECVD reactors (parallel plate- and coaxial electrodes) have shown, that the reactor design (power supply, line connection) sharply influences the large area deposition process. The voltage distribution on the driven elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…1 Generally, these reactors are driven at the standard 13.56 MHz excitation frequency, but there is a strong interest in using higher frequencies because of advantages such as high deposition rate, 2 and reduced sheath voltage and ion energy bombardment. 3,4 However, it has been shown that when higher frequency is combined with large area reactor, standing wave effects become the main source of nonuniformity in conventional capacitively coupled parallel plate reactors, 1,[5][6][7][8][9][10] or in reactors using a ladder electrode. 11 Taking into account the wavelength reduction or worsening effect due to the presence of the plasma, 1,7,9 the standing wave nonuniformity already becomes important when the reactor size is about one tenth of the free space wavelength 0 at the excitation frequency ͑ 0 / 10= 2.2 m at 13.56 MHz, but only 0.3 m at 100 MHz͒.…”
Section: Introductionmentioning
confidence: 99%
“…1 Generally, these reactors are driven at the standard 13.56 MHz excitation frequency, but there is a strong interest in using higher frequencies because of advantages such as high deposition rate, 2 and reduced sheath voltage and ion energy bombardment. 3,4 However, it has been shown that when higher frequency is combined with large area reactor, standing wave effects become the main source of nonuniformity in conventional capacitively coupled parallel plate reactors, 1,[5][6][7][8][9][10] or in reactors using a ladder electrode. 11 Taking into account the wavelength reduction or worsening effect due to the presence of the plasma, 1,7,9 the standing wave nonuniformity already becomes important when the reactor size is about one tenth of the free space wavelength 0 at the excitation frequency ͑ 0 / 10= 2.2 m at 13.56 MHz, but only 0.3 m at 100 MHz͒.…”
Section: Introductionmentioning
confidence: 99%
“…A very high-frequency (VHF; 30-300 MHz) plasma has the advantage of a higher deposition rate and lower ion damage; however, it is difficult to generate a uniform plasma in a large area due to the standing wave and high stray impedance [1]. Silicon films fabricated through PECVD using a VHF plasma have demonstrated a deposition uniformity of ±6.1% over a 50 cm × 60 cm substrate at a frequency of 54.24 MHz using multiple power supplies and a load impedance at the end of the VHF electrode [2] and one of ±18% over a 35 cm × 45 cm substrate at 70 MHz [3]. Takeuchi and co-workers [4] developed a ladder electrode consisting of multiple stainless steel rods and demonstrated hydrogenated amorphous silicon (a-Si : H) deposition at a frequency of 13.56 MHz.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fact that the wavelength of the radio-frequency signal is of the order of the substrate dimensions (3 m at 100 MHz), it can be expected that uniform deposition is more difficult at these high frequencies [477]. In fact, a practical optimum frequency is used around 60-70 MHz [478,479], which provides a good compromise between high deposition rate and attainability of uniform deposition.…”
Section: Viiia1 Generalmentioning
confidence: 99%